2021
DOI: 10.1002/clc.23693
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and 3‐year outcomes of compromised left circumflex coronary artery after left main crossover stenting

Abstract: Background: There are few predictors of decreased fractional flow reserve (FFR) in the left circumflex coronary artery (LCx) after left main (LM) crossover stenting.Objectives: We aimed to determine the predictors for low FFR at LCx and possible treatment strategies for compromised LCx, together with their long-term outcomes. Methods: Altogether, 563 patients who met the inclusion criteria were admitted to our hospital from February 2015 to November 2020 with significant distal LM bifurcation lesions. They und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The ostium of the LCX is the area of the left main which is particularly prone to failure of PCI 30,31 . This is in part due to the increased restenosis rate of ostial lesions per se but also the common presence of calcification restricting stent expansion 32 .…”
Section: Mode Of Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…The ostium of the LCX is the area of the left main which is particularly prone to failure of PCI 30,31 . This is in part due to the increased restenosis rate of ostial lesions per se but also the common presence of calcification restricting stent expansion 32 .…”
Section: Mode Of Clinical Presentationmentioning
confidence: 99%
“…26 Indeed, LMCA lesion location per se is an independent correlate of significant coronary calcification. 27 The ISAR-LEFT-MAIN trial demonstrated the prognostic role of anatomical complexity showing a significantly lower TLR rate at 3 years in patients with SYNTAX scores ≤22 as compared to patients with intermediate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and high (≥33) scores (9.2% vs. 14.9% vs. 13.0%, respectively, p = 0.008). 24 Moreover, the involvement of "true" ULMCA bifurcation (Medina 1,1,1) was an independent predictor of TLR (HR 2.12 95% CI: 1.19-3.77, p = 0.011).…”
Section: Anatomical Factorsmentioning
confidence: 99%
See 1 more Smart Citation